Phase I, First‐in‐Human, Dose‐Escalation Study to Evaluate the Safety, Tolerability, and Pharmacokinetics of Vorolanib in Patients with Advanced Solid Tumors. (26th November 2018) - Bendell, Johanna C.; Patel, Manish R.; Moore, Kathleen N.; Chua, Cynthia C.; Arkenau, Hendrik‐Tobias; Dukart, Gary; Harrow, Kim; Liang, Chris
Abstract: Lessons Learned: Pharmacokinetic results underscore that the vorolanib (X‐82) study design was successful without the need for further dose escalation beyond 400 mg once daily (q.d.). Therefore, the recommended dose of X‐82 as a single agent in patients with advanced cancer is 400 mg q.d. Background: Vorolanib (X‐82) is a novel, oral, multikinase vascular endothelial growth factor (VEGF) receptor/platelet‐derived growth factor (PDGF) receptor inhibitor that was developed on the same chemical scaffold as sunitinib, but designed to improve upon the safety profile while maintaining the efficacy of sunitinib. By targeting the VEGF and PDGF receptors, X‐82 was expected to disrupt tumor angiogenesis and be active in a broad spectrum of solid tumors. Therefore, we determined the maximum tolerated dose (MTD) and characterized the preliminary pharmacokinetics and clinical tumor response of X‐82 as a single agent in patients with advanced solid tumors. Methods: Adult patients with advanced solid tumors received X‐82 as tablets or capsules (once daily [q.d.] or b.i.d.) every 4 weeks. Patients were evaluated for response every 8 weeks, and continued treatment until disease progression or intolerable toxicity. Results: Fifty‐two patients received study treatment in 17 cohorts. X‐82 capsule dosing was as follows: cohorts 1–6 (20–400 mg q.d.) and cohorts 7–8 (140–200 mg b.i.d.). Patients in cohorts 9–17 received 50–800 mg q.d. tablet dosing. The median time on treatment was 58 days. X‐82 blood pharmacokinetics appeared dose‐independent with a t 1/2 of 5.13 hours and 6.48 hours for capsule and tablet formulations, respectively. No apparent accumulation was observed after 21 days of daily dosing. Conclusion: X‐82 had a safety profile consistent with its mechanism of action. It has a short half‐life and was well tolerated by most patients. Study enrollment ended prior to the determination of the MTD because of the apparent saturation of absorption at 400–800 mg. The recommended dose of X‐82 as a single agent in patients with advanced cancer is 400 mg q.d.